Influence of electric fields on the structure of chitosan edible coatings - Souza, B. W. S. (2010)
The aim of this work was to evaluate the effect of electric fields applied at different field strength values on mechanical and thermal properties of chitosan films/coatings (obtained from lobster of the Cuban coasts). XRD analyses indicated that electrically treated chitosan films exhibited a more ordered structure and a clearly higher crystallinity when compared with non-treated films, thus displaying significant effects on the value of the crystallinity index (CI). SEM micrographs evidenced that the surface morphology of chitosan films was influenced by the electric field. In fact, the electric field treatment led to a structure with more regular layers as can be seen in the cross-sections of the films observed under SEM. The application of the electric field to chitosan film-forming solutions resulted in an increase of the tensile strength (c.a. 9%) and elongation-at-break (c.a. 18%) of the corresponding chitosan films. The reported results demonstrate that the application of an electric field to film-forming solutions of chitosan is an interesting instrument to taylor relevant properties of the films or coatings produced from them.